Fetal nuchal translucency scan and early prenatal diagnosis of chromosomal abnormalities by rapid aneuploidy screening: observational study - Chitty, Lyn S; Kagan, Karl O; Molina, Francisca S; Waters, Jonathan J; Nicolaides, Kypros H (BMJ, 2006)
Abstract Objective To investigate an approach for the analysis of samples obtained in screening for trisomy 21 that retains the advantages of quantitative fluorescent polymerase chain reaction (qf-PCR) over full karyotyping and maximises the detection of clinically significant abnormalities. Design Observational study. Setting Tertiary referral centre. Subjects 17 446 pregnancies, from which chorionic villous samples had been taken after assessment of risk for trisomy 21 by measurement of fetal nuchal translucency (NT) thickness at 11 to 13+6 weeks of gestation. Interventions Analysis of chorionic villous samples by full karyotyping and by qf-PCR for chromosomes 13, 18, 21 X and Y. Main outcome measure Detection of clinically significant chromosomal abnormalities. Results The fetal karyotype was normal in 15 548 (89.1%) cases and abnormal in 1898 (10.9%) cases, including 1722 with a likely clinically significant adverse outcome. Karyotyping all cases would lead to the diagnosis of all clinically significant abnormalities, and a policy of relying entirely on qf-PCR would lead to the diagnosis of 97.9% of abnormalities. An alternative strategy whereby qf-PCR is the main method of analysis and full karyotyping is reserved for those cases with a minimum fetal NT thickness of 4 mm would require full karyotyping in 10.1% of the cases, would identify 99.0% of the significant abnormalities, and would cost 60% less than full karyotyping for all. Conclusions In the diagnosis of chromosomal abnormalities after first trimester screening for trisomy 21, a policy of qf-PCR for all samples and karyotyping only if the fetal NT thickness is increased would reduce the economic costs, provide rapid delivery of results, and identify 99% of the clinically significant chromosomal abnormalities.